2021
DOI: 10.2147/copd.s226688
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Dual Phosphodiesterase 3/4 Inhibitors for the Treatment of Patients with COPD: A Short Review

Abstract: Current pharmacological treatments for chronic obstructive pulmonary disease (COPD) are mostly limited to inhaled bronchodilators and corticosteroids. Azithromycin can contribute to exacerbation prevention. Roflumilast, a phosphodiesterase (PDE) 4 inhibitor administered orally, also prevents exacerbations in selected patients with chronic bronchitis, recurrent exacerbations, severe airflow limitation and concomitant therapy with long-acting inhaled bronchodilators. This outcome likely results from anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…81 PED3 is widely distributed in T lymphocytes, and lymphocyte function can be regulated by inhibition of PED3; inhibiting PED4 can reduce IL-4 and 5 gene expression in TH2 cells, decreases levels of inflammatory factors and has a synergistic effect with PED3 inhibitors in T cells. 82 Clinical evidence 83,84 also indicated that PED3/4 inhibitors (RPL-5 and roflumilast) both improve the lung function in COPD patients. However, when these patients simultaneously use standard bronchodilators, the function of RPL-554 and roflumilast benefits little.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…81 PED3 is widely distributed in T lymphocytes, and lymphocyte function can be regulated by inhibition of PED3; inhibiting PED4 can reduce IL-4 and 5 gene expression in TH2 cells, decreases levels of inflammatory factors and has a synergistic effect with PED3 inhibitors in T cells. 82 Clinical evidence 83,84 also indicated that PED3/4 inhibitors (RPL-5 and roflumilast) both improve the lung function in COPD patients. However, when these patients simultaneously use standard bronchodilators, the function of RPL-554 and roflumilast benefits little.…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…In 4-week, phase II clinical trials, nebulized drug given twice a day alone or in combination with other bronchodilators, showed sustained bronchodilation and improvement in FEV1, improvement in symptoms judged by questionnaires, improvement in residual volumes and COPD symptoms. 19 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Although phosphodiesterase 4 (PDE4) inhibitors appear to be potential agents for asthma and chronic obstructive pulmonary disease (COPD) [37], they have also begun to be investigated for CNS diseases, such as memory impairments or multiple sclerosis, among others [38]. This is the case for compound 23 (Figure 7a), whose fumarate salt was considered as a potential candidate for the treatment of Alzheimer's disease [39].…”
Section: Pde4 Inhibitormentioning
confidence: 99%